Fattening performance, slaughter and carcass characteristics of akkaraman lambs at different slaughter weights - Emine Hesna Şahin; Ali Akmaz (Eurasian Journal of Veterinary Sciences)
This study was carried out to investigate the fattening performance and carcass traits of Akkaraman male lambs at slaughter weight of 35, 40. 45 and 50 kg. The material of the research consisted of 55 Akkaraman male lambs aging from 2.5 to 3 months old with an average body weight of 21 kg. Dunng the experiments lambs were ted with wheat hay (100 g /head/day) and consantrates ad libitum. The data were analyzed by one-way analysis of variance (ANOVA) test. The period acquired lor reaching live weights, average daily gains at the fattening period and feed/gain ratios were found as 70.31 day. 199.74 g and 6,17 kg for 35 kg; 87.36 day, 224.30 g and 5.77 kg (or 40 kg; 108.14 day, 225.34 g and 6.12 kg for 45 kg; 134.07 day, 216.37 g and 6.62 kg tor 50 kg, respectively. The carcasses were seperated into five major cuts including leg, shoulder, back, loin and others. To determine carcass composition, shoulder cuts were dissected. The cold carcass weight, dressing percentage, the ratios of teg, shoulder, loin and tail fal weights were tound as 16.18 kg, 46.33%, 30.14%, 15.17%, 6.42% and 16.18% for 35 kg; 18.18 kg, 46,02%, 29.42%, 14.57%, 6.70% and 15.60% lor 40 kg; 21.28 kg. 47.25%, 28.26%, 14.12%, 6.25% and 17.78% lor 45 kg; 25.72 kg, 51.58%, 27.12%, 13,43%, 6.79% and 21.41% lor 50 kg respectively. The percentages of lean, fat and bone at shoulder cuts were found as 65.07%, 14.33% and 20,60% for 35 kg; 65.33%, 13.31% and 21.36% (or 40 kg; 64.09%, 15.62% and 20.29% for 45 kg; 61.83%, 18.77% and 19.40% for 50 kg respectively. As a result; slaughter weight of 45 kg show the maximum values about the investigated characteristics than the other slaughters group was found.